Nonfragile H∞ Observer Design for a Class of One-Sided Lipschitz Uncertain Systems with Quantization - El Haiek, B (Institute of Electrical and Electronics Engineers Inc., 2025)
This paper addresses the design of nonfragile observers for a class of one-sided Lipschitz nonlinear systems with quantization. The measured output signals undergo quantization through a static quantizer before transmission. To achieve this, the one-sided Lipschitz condition and the quadratic inner-bounded condition are used to derive less conservative criteria for observer design. By applying a decoupling technique, sufficient conditions are expressed in the form of linear matrix inequalities (LMIs) to guarantee the robustness of the closed-loop system with quantization. Additionally, the observer gain is calculated. The proposed approach is validated using a practical example involving a mechanical rotating system. © 2025 IEEE.